Shikonin Promotes Apoptosis and Attenuates Migration and Invasion of Human Esophageal Cancer Cells by Inhibiting Tumor Necrosis Factor Receptor-Associated Protein 1 Expression and AKT/mTOR Signaling Pathway - Jingrong Huang (Hindawi Limited, 2021)
The aim of this study was to investigate the anticancer effects of shikonin on esophageal cancer (EC) cells and explore the underlying molecular mechanism by identifying dysregulation in shikonin-induced tumor necrosis factor receptor-associated protein 1 (TRAP1) expression. The 3-(4, 5-dimethylthiazol-2-Yl)-2, 5-diphenyltetrazolium bromide assay and EDU assay were performed for cell viability determination. The reactive oxygen species level and mitochondrial membrane potential were evaluated using flow cytometry. The protein expression was detected using Western blot. In addition, cell migration and invasion were estimated. These results demonstrated that shikonin inhibited EC cell growth in a concentration-dependent manner and induced apoptosis through activation of the intracellular apoptotic signaling pathway. Moreover, TRAP1 downregulation promoted shikonin-induced reactive oxygen species release, whereas TRAP1 upregulation blocked it. Meanwhile, shikonin significantly promoted mitochondrial depolarization, accompanied by a large release of cytochrome C. Conversely, shikonin significantly decreased adenosine 5′-triphosphate release, demonstrating a significant intervention in the process of the glucose metabolism. In addition, not only shikonin but also short hairpin RNA (shRNA)-TRAP1 inhibited EC cell migration and invasion. shRNA-TRAP1 enhanced the inhibitory effect of shikonin on matrix metalloproteinase (MMP)2 and MMP9 expression. More interestingly, we demonstrated that shRNA-TRAP1 played a synergistic role in shikonin-mediated regulation of protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling. Collectively, shikonin promoted apoptosis and attenuated migration and invasion of EC cells by inhibiting TRAP1 expression and AKT/mTOR signaling, indicating that shikonin may be a new drug for treating EC.